2021
DOI: 10.21203/rs.3.rs-607376/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Heart has Intrinsic Ketogenic Capacity that is Facultatively Upregulated in Heart Failure with Preserved Ejection Fraction

Abstract: Heart Failure with preserved Ejection Fraction or ‘HFpEF’ is now the most common type of heart failure worldwide, with considerable morbidity and mortality, and with no effective pharmacotherapies. For the first time, we show that the human and murine HFpEF heart have impaired uptake of ketone bodies, and reveal an intrinsic capacity of human and murine hearts to generate their own ketones via the canonical rate-limiting ketogenic enzyme, 3-hydroxy-3-methylglutaryl CoA synthase 2 (HMGCS2). We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…A recent study in cardiac hypertrophy reported SIRT3dependent enhancement of ketone body metabolism via AMPKmediated increase in the levels of monocarboxylic transporters 1 (MCT1) and 3-oxoacid CoA-transferase (OXCT1) (60). Another study reported that a key enzyme in ketogenesis, HMGS2 is dramatically upregulated in heart failure with preserved ejection fraction (HFpEF) (142). Its specific activity is, however, impaired in these hearts.…”
Section: Sirt3 In Ketone Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in cardiac hypertrophy reported SIRT3dependent enhancement of ketone body metabolism via AMPKmediated increase in the levels of monocarboxylic transporters 1 (MCT1) and 3-oxoacid CoA-transferase (OXCT1) (60). Another study reported that a key enzyme in ketogenesis, HMGS2 is dramatically upregulated in heart failure with preserved ejection fraction (HFpEF) (142). Its specific activity is, however, impaired in these hearts.…”
Section: Sirt3 In Ketone Metabolismmentioning
confidence: 99%
“…HFpEF myocardium is also characterized by a net reduction in NAD + /NADH ratio and subsequently in SIRT3 expression. Since ketogenesis may serve as an essential energy source in failing hearts, SIRT3-dependent upregulation of ketogenesis may function as a "rescue strategy" in heart failure (142,143).…”
Section: Sirt3 In Ketone Metabolismmentioning
confidence: 99%
“…Fragmentary extrahepatic ketogenesis has been reported in tumour cells ( 43 ), astrocytes of the central nervous system (CNS) ( 44 ), renal cells ( 45 ), retinal pigment epithelium ( 46 ), or other cells with an unusual expression of mHMGCS2 ( 47 , 48 ), ketogenesis was also observed. However, in the physiological state, no extrahepatic tissue presents a higher steady-state ketone body concentration than in the circulation ( 49 ), indicating that the extrahepatic ketogenesis does not influence the circulating ketone body concentration.…”
Section: Endogenous Ketogenesismentioning
confidence: 99%